Exploration of 5-Hydroxybowdichione Flavonoids As Inhibitors of Dengue Virus Ns5 RNA-Dependent RNA Polymerase Using Molecular Docking Approach - Arshita Jindal (International Journal of Genetic Modifications and Recombinations, 2023)
Objectives: Human lives are now seriously threatened by dengue fever, which is brought on by the dengue virus (DENV). Aedes aegypti mosquitoes, which reproduce in still water, are the primary vectors of the arboviral virus known as dengue. It is well-recognized that phytochemicals have a high potential to eliminate bacterial, viral, and fungal infections in people. Thus, it demonstrates its inhibitory effects on the dengue virus. This study identifies some of the 5-hydroxybowdichione flavonoids' natural dengue virus inhibitors. Methods: 5-hydroxybowdichione flavonoids were employed in a computational technique to evaluate the effective inhibitor against dengue virus NS5 RNA-dependent RNA polymerase. 15 flavonoids in total, including 5-hydroxybowdichione and its derivatives, were chosen. The findings analysis was carried out using a variety of methods and instruments. To identify the phytocompounds, PubChem was employed. Protein was retrieved from the Protein Data Bank and confirmed using a variety of tools, including the BIOVIA discovery studio software, PDBsum generates, and the Swiss model. The PyRx software was used to carry out the molecular docking. For the pharmacological research, ADMET studies on these flavonoids were conducted. Results: The ligands Cudraflavone-C, Paratocarpin-B, Paratocarpin-C, and Shancio-H have the lowest binding affinities and may have an inhibitory impact on DENV, according to the ADMET analysis and docking data. These ligands have the best ADMET characteristics and pose the least amount of hazardous risk. Conclusion: The best binding affinity for protein is -9.7, and it belongs to the ligand Shanciol-H. In vitro studies can be used to learn more about these substances
Keywords: 5-hydroxybowdichione; ADMET; Dengue virus; RNA-dependent RNA polymerase; molecular docking; phytocompounds